VD_FINDINFO Faillite / 2015 / 19 vom 1. Juli 2015 - VD Tribunal cantonal (2015)
FICTION DE LA NOTIFICATION, NOTIFICATION DE LA DÉCISION, ENVOI RECOMMANDÉ | 174 al. 1 LP, 174 LP, 138 al. 3 let. a CPC (CH)